Research on Key Technologies of Elastic Satellite Optical Network Based on Optical Service Unit - Wei Zhou; Bingli Guo; Qingsong Luo; Boying Cao; Bitao Pan (Applied Sciences)
With the advent of 6G technologies, satellite communication networks are in urgent need of innovative bearer technologies to meet the demands of government and enterprise private lines as well as computing power networks. We propose optical service unit-based optical inter-satellite links (OISL-OSU) as a solution to address the current limitations in fine-grained service bearing within optical transport networks (OTNs), thereby enhancing the flexibility and efficiency of satellite optical networks. Comparative tests were conducted between OISL-OSU and existing packet-switching technologies in multi-service satellite optical transport networks. Through hardware-in-the-loop simulation verification, key performance indicators such as delay optimization, bandwidth utilization rate, and flexible resource adjustment capability were systematically evaluated. Experimental results demonstrate that OISL-OSU technology exhibits superior performance in delay optimization and fine-grained service bearing. The flexible mapping and multiplexing mechanism of OISL-OSU significantly improves resource utilization efficiency, decreases transmission delay, and strengthens hard-pipe connection capabilities.